PENGARUH GAYA KEPEMIMPINAN DAN STRESS KERJA TERHADAP KINERJA PEGAWAI BBMKG WILAYAH II TANGERANG SELATAN - Rosih, Rosih; Mulyadi Mulyadi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The purpose of this study was to determine the effect of leadership style and work stress on the performance of BBMKG Region II South Tangerang employees both partially and simultaneously. The method used in this study is an associative quantitative method. The population of BBMKG Region II South Tangerang was 70 respondents. The sample used in this study used a saturated sample, which means it is the same as the population of 70 people. The analysis in this study used the SPSS program version 25. The data analysis method used a simple linear regression test, multiple linear regression, correlation coefficient, determination coefficient, partial T test and simultaneous F test. The results of this study indicate that: There is a partial significant influence of leadership style on the performance of BBMKG Region II South Tangerang employees. This can be proven because the leadership style variable (X1) has a calculated T value of 11.208 > T table 1.995 with a significance level of 0.000 <0.05. There is a partial significant influence of work stress on the performance of BBMKG Region II South Tangerang employees. This can be proven because the work stress variable (X2) has a calculated T-value of 6.220 > T-table 1.995 with a significance level of 0.000 < 0.05. There is a significant simultaneous influence of leadership style and work stress on employee performance at BBMKG Region II South Tangerang. This is proven by the calculated F-value of 64.506 > F-table 3.130 with a significance level of 0.000 < 0.05. The results of the coefficient of determination test are indicated by an R- square value of 0.658, which means that the leadership style (X1) and work stress (X2) variables contribute 65.8% to employee performance (Y), while the remaining 34.2% is due to other variables not examined in this study.